TRANSFORMASI PENDIDIKAN ABAD 21: RELEVANSI FILSAFAT PENDIDIKAN DENGAN PEMBENTUKAN KARAKTER NASIONAL - Jamaluddin, Nurbina Septiani; Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Globalization and technological development in the 21st century bring new challenges to the education system, especially in shaping the character of the younger generation. This article discusses the relevance of educational philosophy in shaping a resilient and dignified national character. Through a literature study approach, it analyzes the concept of educational philosophy which includes goals, values, and learning methods. Philosophical approaches such as humanism, existentialism, pragmatism, and nationalism prove relevant in instilling national values such as integrity, tolerance, and love for the country. Implementation strategies include curriculum integration, moral role models, contextual learning, and strengthening multiculturalism. The results show that philosophy of education is able to create a generation that is academically competent, moral, and able to adapt to global challenges without losing cultural identity. This conclusion emphasizes the importance of philosophy of education as a strategic foundation in building the character of a sovereign and dignified nation.